A positioning technique for closed intramedullar nailing of tibia fractures - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Background. We described a method of positioning the patient on the standard operation table that enables manual traction and equipment that is available in almost all operating theaters and compared it with regular positioning technique. Methods: Eighty two patients with unstable unilateral tibia fractures were evaluated and treated in the author's clinic between July 2002 and June 2006. The average age of the patients was 40.6 (29-65) years. The surgical indications included uncomplicated closed fractures, fractures in patients with multiple injuries, and inability to maintain a satisfactory closed reduction. Forty-two fractures that were operated with the new technique and meet these criteria's were included in the study. All operations were performed on normal operation tables. Results: There was not any case of failure related with the nailing and the presented positioning technique. Intraoperative reduction was achieved with closed method in all patients. In 10 patients, satisfactory reduction was achieved with the help of polar screws in 2 patients and cable system in 8 patients. Anatomic reduction was obtained in the rest of 32 patients. There were no cases of compartment syndrome diagnosed postoperatively in both injured and uninjured side. There were also no neurologic complications and postoperative infection formation related to surgery. Conclusion: The advantages of this technique is that, it allows precise reduction, control of rotation, and easy imaging access, without increasing operating or screening time and complication.
Keywords: intramedullar nailing; tibia fractures; positioning; TRACTION; FRAME